DETERMINAN KEJADIAN TB PARU PADA USIA PRODUKTIF - Amaliah, Lili; Rosdiana, Rosdiana; Wahyudi, Teguh; Wirda, Wirda (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Abstract: Tuberculosis (TB) is a direct infectious disease caused by Mycobacterium Tuberculosis. Based on document searches, in 2023, Putri Ayu Health Center was one of the health centers with the highest incidence of TB and experienced an increase in cases compared to the previous year, reaching 95 cases. The purpose of the study was to determine the determinants of the incidence of pulmonary TB in productive age. The research design used in this study was Case Control. The research was conducted in the working area of the Putri Ayu Health Center. The research was conducted from May to July 2024. The study population was all cases of Tb in the Putri Ayu Health Center work area totaling 97 people. The research sample has a ratio of 1: 1 so that the sample amounted to 114 people. The sampling technique used in this study was Simple Random Sampling. Data analysis was done univariate and bivariate. The results showed a relationship between income (p value: 0.031) and contact history (p value: 0.024) to the incidence of TB. It is recommended that the community, especially those with low income and a history of TB contact, should receive more attention from health workers to ensure TB screening in communities with risk factors and with TB symptoms.Keywords: Income, Contact History, Tuberculosis.